DEKONSTRUKSI PSEUDO-SPIRITUAL MASYARAKAT BERAGAMA DI INDONESIA - Andi Thamrin (Universitas Islam Negeri Imam Bonjol Padang, 2019)
The dynamics of human relations with religious and cultural backgrounds are increasingly complex and are more likely to arise in the presence of various conflicts. Examining the fulfillment of the solutions needed for the nation's children through various forms of education to instill a pure understanding of spirituality that no longer matches the physical level. By using a method library research, articles that need to be done in providing education for our young generation in terms of communication on religious development, including the role of the government as the relevant authority and religious leaders, the community, and communication media in perpetuating this development. Contacts related to intercultural and cross-cultural and religion in Indonesia. The multi-track communication model as one of the various integrated educational tools is needed in this regard. How to direct others about the information and thoughts of people with different backgrounds from each individual can be minimized related to this term.